Pengaruh Durasi Penyimpanan Terhadap Kualitas Packed Red Cell Di UDD PMI Kota Semarang - Subekti; Galih Hari Wijaya; Anna Kartika Yuli Astuti; Widoyono (LPPM POLBITRADA, 2024)
Packed Red Cell (PRC) storage affects the stability of erythrocytes, this condition can pose a risk of decreased hemoglobin diffusion into tissues due to the storage process. The role of PRC to increase hemoglobin in patients is inseparable from the fact that the product experiences a decrease in quality during storage. This study aims to determine the effect of Packed Red Cell (PRC) storage duration for 21, 28, 35 days on the quality of PRC carried out at the UDD PMI Semarang City. The research method was Quasi Experiment study, with a modification of Time Series Design using the Quota sampling technique. PRC research samples were taken at the UDD PMI Semarang City in July-September 2023 with a total of 24 bags. The independent variable is the duration of PRC storage, the dependent variable is the quality of PRC. Based on the results of this study, it shows that hemoglobin (Hb) and hematocrit (Ht) increased from day 21 to day 35 but not significantly (P> 0.05), while hemolysis showed an increase from day 21 to day 35 significantly (P <0.05) but the value is still within normal limits. Correlation value between Hb and PRC storage duration; r = 0.948, Ht with PRC storage duration; r = 0.202, hemolysis with PRC storage duration; r = 0.000. The conclusion of this study is that there is no significant effect on hemoglobin and hematocrit levels of PRC products with storage days 21, 28, and 35, and there is a significant effect on hemolysis levels but still within normal limits according to the requirements of the Minister of Health. Suggestions for further research with a better number of samples, types of examinations and designs to determine the standards and storage time limits for PRC. Keywords: Quality, Packed Red Cell, Storage